2008
DOI: 10.1007/s11370-008-0016-5
|View full text |Cite
|
Sign up to set email alerts
|

Using dialog and human observations to dictate tasks to a learning robot assistant

Abstract: Robot assistants need to interact with people in a natural way in order to be accepted into people's day-today lives. We have been researching robot assistants with capabilities that include visually tracking humans in the environment, identifying the context in which humans carry out their activities, understanding spoken language (with a fixed vocabulary), participating in spoken dialogs to resolve ambiguities, and learning task procedures. In this paper, we describe a robot task learning algorithm in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The notion of spatial description clauses is influenced by many similar formalisms for reasoning about the semantics of natural language directions [7], [8], [9], [10], [11], [12]. The structure of the spatial description clause builds on the work of Landau and Jackendoff [13], and Talmy [14], providing a computational instantiation of their formalisms.…”
Section: Related Workmentioning
confidence: 99%
“…The notion of spatial description clauses is influenced by many similar formalisms for reasoning about the semantics of natural language directions [7], [8], [9], [10], [11], [12]. The structure of the spatial description clause builds on the work of Landau and Jackendoff [13], and Talmy [14], providing a computational instantiation of their formalisms.…”
Section: Related Workmentioning
confidence: 99%
“…Forbes et al [9] implemented a set of robust parametrized motion procedures on a PR2 mobile manipulator and converted the NL sentences into intended procedures and their parameter instantiations. Rybski et al [10] designed a task representation called Directed Acyclic Graph (DAG), which includes a preconditioned list of the behavior, the behavior and the link to the next behavior. The outputted formal representations are action plans in fact, and can be implemented by the robot sequentially.…”
Section: Related Workmentioning
confidence: 99%
“…It has been demonstrated that learning can be used to infer meanings from spoken utterances [12,13]. These scenarios are usually restricted to a constrained set of vocabulary or using manual annotation to improve the learning algorithm.…”
Section: Passive Sensing Vs Active Teachingmentioning
confidence: 99%